The Effects of Aerobics And Soy Milk on Triglycerides and Menopausal Symptoms - Dhea Novita; Rr Sri Endang Pujiastuti; M Choiroel Anwar; Septiwiyarsi (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
The decrease in estrogen production during menopause affects the quality of life with the emergence of menopausal symptoms and increases the risk of cardiovascular disease. After the menopause transition, when estrogen levels in a woman's body decrease, the risk of cardiovascular disease increases rapidly, and at older ages, women have the same or even slightly higher risk of cardiovascular events as men. Low-impact aerobic exercise for 20-30 minutes, three times a week for two weeks, will have a positive effect on quality of life. The administration of soy has the potential to reduce menopausal symptoms and complaints due to its phytoestrogen content. Phytoestrogens have a structure and function similar to estrogen. Phytoestrogens are also known to have potential as an alternative hormone replacement therapy to alleviate premenopausal symptoms such as hot flushes caused by the decrease in estrogen hormone levels in the body. The objective of this study is to specifically determine the effects of low-impact aerobic exercise and soybean milk on triglyceride levels and menopausal symptoms  in menopausal groups. This research was a Quasi-Experiment with a pretest-posttest design with a control group. The result shows that low-impact aerobic exercise and soy milk have an effect on reducing triglyceride levels with a p-value of 0.000 <0.05 and a mean delta reduction of 72.0. It can be concluded that there is an effect of low-impact aerobic exercise and soy milk on triglyceride levels and reduce menopausal symptoms in the menopausal group.